Taming Challenging Radical-Based Convergent Paired Electrolysis with Dual-Transition-Metal Catalysis - Li, Liubo; Fu, Niankai (Synlett, 2023)
The past few years have witnessed a renaissance of electrochemistry in organic synthesis. This green technology replaces chemical oxidants or reductants with inexpensive electricity. Paired electrolysis refers to processes in which reactions at both electrodes are desirable. These maximize the energy economy by avoiding the waste of electrical power on sacrificial reactions. Convergent paired electrolysis is a special case in which reactive intermediates are generated simultaneously at both electrodes and then coupled. However, radical-based reactions of this type remain underexploited. The incorporation of transition-metal catalysis could be beneficial by modulating the formation and utilization of highly reactive radical species. In this article, we introduce our most recent successful implementations of this strategic design.1 Introduction2 Ce/Ni Dual-Catalytic Decarboxylative Arylation3 Fe/Ni Dual-Catalytic Esterification of Aryl Halides4 Conclusion.
Keywords: convergent paired electrolysis; electrochemistry; electrocatalysis; radical reaction; transition-metal catalysis